The analysis of possibilities to enter the ports of the Baltic sea for big container ships - Paulauskas, Vytautas; Paulauskas, Donatas; Plačienė, Birutė (Transport, 2002)
The article investigates technical, economical and organizational possibilities to enter the Baltic ports for container ships as the result of economic globalization and the increase of transcontinental container transportation.First Published Online: 19 Oct 2011